SALSA: A Scheduling Algorithm for LoRa to LEO Satellites - Afhamisis, Mohammad; Palattella, Maria Rita (IEEE access, 2022)
Satellites are going to revolutionize the Internet of Things (IoT) connectivity enabling the ubiquitous coverage targeted by 5G and upcoming 6G networks. While the potentials of satellite IoT are unquestionable, many challenges still remain unsolved. In the present work, we design a Long Range Wide Area Network (LoRaWAN) with mobile gateways (GWs) installed on Low Earth Orbit (LEO) satellites. We address synchronization issues due to intermittent link availability between the End Devices (EDs) and the GW, and we propose a Scheduling Algorithm for LoRa to LEO Satellites (SALSA). SALSA ensures reliable communication, avoiding packets drops and packet collisions, by using a Time Division Multiple Access (TDMA) approach, rather than classic ALOHA-based LoRa. The uplink transmissions of the EDs are scheduled considering the satellite availability period, the satellite footprint, and the specific visit time for each ED. Two different policies are proposed: a First Come First Served (FCFS), and a FAIR policy. Simulation results, obtained in real conditions, with real satellites visibility, demonstrate the better performance achievable with SALSA (regardless of the policy) compared to standard LoRa. The FAIR policy outperforms the FCFS policy by giving all the EDs an equal chance to transmit, even to those that are visited last by the satellite. The performance of SALSA can be further improved considering larger constellations of LEO satellites.